INFLUENCE OF OPERATING CONDITIONS AND THE CAPACITY OF A CAULDRON FIRETUBE IN ENERGY SAVING - Huapaya Barrientos, José (2003)
The work highlights the importance of optimal use of energy inputs in industrial activity, such as a need for international and national competitiveness. Fuel economy is quantified annually and the economic benefit that companies fail to recover the energy of the purges in the operation of a steam generator is checked. A real case is discussed in order to validate the aforementioned items.